Endomyocardial fibrosis in Sub Saharan Africa: The geographical origin, socioeconomic status, and dietary habits of cases reported in Yaounde, Cameroon - David Chelo; Felicitee Nguefack; Hubert D Mbassi Awa; Samuel Kingue (Wolters Kluwer Medknow Publications, 2015)
Background : Endomyocardial fibrosis (EMF) is a neglected heart condition of the inter-tropical regions. Numerous hypotheses suggest a relationship between its geographical distribution in the affected regions and other etio-pathogenic factors such as dietary habits, infectious causes, and geochemical causes. Knowledge of its epidemiology in Cameroon remains limited, which is why we decided to describe the profile of a paediatric series of EMF in Yaoundé. Patients and Methods : A retrospective study was carried out on EMF in 54 patients diagnosed from 1 January 2006-31 December 2014 in a Paediatric Centre of Yaoundé. Diagnosis was mainly echocardiographic. We compiled data on the geographic origins of the patients, their dietary habits and the socioeconomic profile of their families. Results : The patients' ages ranged from 2 to 17 years, most of whom (83.3%) were between 5 and 15 years. For geographical distribution, all came from three tropical forest zones where they have lived since their childhood. These were Center (32/54), South (12/54), and East (10/54). All families had a moderate income, consumed tubers at least twice a week especially cassava (43/54) and had low sources of proteins. Conclusion : Apart from geographical similarities all patients of our series shared the same dietary habits. Our study was conducted in a hospital setting; therefore a screening of the disease in the whole national territory would enable a more reliable mapping.